2019
DOI: 10.21037/hbsn.2019.02.06
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and severity of post-hepatectomy bile leaks is affected by surgical indications, preoperative chemotherapy, and surgical procedures

Abstract: Background: Bile leaks are one of the most common complications after liver resection. The International Study Group of Liver Surgery (ISGLS) established a uniform bile leak definition including a severity grading. However, a risk factor assessment according to ISGLS grading as well as the clinical implications has not been studied sufficiently so far. Methods: The incidence and grading of bile leaks according to ISGLS were prospectively documented in 501 consecutive liver resections between July 2012 and Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…Using the definition of the International Study Group of Liver Surgery (ISGLS), the incidence of PHBF ranges from 4.4% to 27.2% [ 95 , 96 ]. Spetzler et al reported that in patients who required neoadjuvant chemotherapy, liver fragility and major hepatectomy are predicted risk factors for PHBF [ 97 ]. Remarkably, these findings are consistent with previous studies [ 98 , 99 , 100 ].…”
Section: Postoperative Complicationsmentioning
confidence: 99%
“…Using the definition of the International Study Group of Liver Surgery (ISGLS), the incidence of PHBF ranges from 4.4% to 27.2% [ 95 , 96 ]. Spetzler et al reported that in patients who required neoadjuvant chemotherapy, liver fragility and major hepatectomy are predicted risk factors for PHBF [ 97 ]. Remarkably, these findings are consistent with previous studies [ 98 , 99 , 100 ].…”
Section: Postoperative Complicationsmentioning
confidence: 99%
“…For major liver resections, the risk of liver failure and bile leak is increased. 52 The liver itself might be cirrhotic, which can predispose to both post-operative ascites and haemorrhage after open hepatectomy. Conversely, in cirrhotic patients undergoing MIS liver resections, there is preservation of porto-systemic shunts with no increase in portal pressure and subsequent reduction of post-operative ascites and bleeding.…”
Section: -45mentioning
confidence: 99%
“…Patients with low risk of postoperative bile leak such as those undergoing left lateral resections and benign lesions resections would benefit from avoiding routine drains in minimizing retrograde infections and promoting postoperative mobility. 20 Both, PHLF and bile leak are classified into three grades as described in Table 3 .…”
Section: P Ancreasmentioning
confidence: 99%